WAPENSTILSTANDSDAG - Huidamen, J-M. (Scientia Militaria - South African Journal of Military Studies, 2012)
The writer paints a picture of what Armistice Day, 11 November 1918 was like. Included are glimpses of the state in which the warring nations found themselves on this date, and the ways in which the restoration of peace was greeted in the various capitals. In conclusion, reference is made to the Armistice Day remembrance services which are conducted every year in most South African centres under the auspices of the MOTH organisation.